2021
DOI: 10.3390/ani11082205
|View full text |Cite
|
Sign up to set email alerts
|

Radiogrametric Analysis of the Thoracic Limb Phalanges in Arabian Horses and Thoroughbred Horses

Abstract: In this study, it was aimed to determine the statistical differences between Arabian horses and Thoroughbred horses based on X-ray images of forelimb digital bones. Latero-medial X-ray images of digital bones of thoracic limbs were taken of 25 Arabian horses and 50 Thoroughbred healthy horses. The difference between males and females within the breed was statistically analyzed as well. Nine measurements and three indexes taken from phalanges of thoracic limbs were used. Thoroughbred horses did not differ signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…(2017) and Szara et al. (2003) but also from studies performed with measurements according to radiographic images (Eneroth et al., 1999; Gündemir et al., 2021; Limmanont et al., 2019; Oheida et al., 2019; Uzuner et al., 2016).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2017) and Szara et al. (2003) but also from studies performed with measurements according to radiographic images (Eneroth et al., 1999; Gündemir et al., 2021; Limmanont et al., 2019; Oheida et al., 2019; Uzuner et al., 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Osteometric differences between males and females, as well as differences between species have been examined directly in the skeletal bones of the limbs as well as in the skull bones of various animals in studies conducted by Gündemir et al (2020), Kobryńczuk et al (2008), Nganvongpanit et al (2017) and Szara et al (2003) but also from studies performed with measurements according to radiographic images (Eneroth et al, 1999;Gündemir et al, 2021;Limmanont et al, 2019;Oheida et al, 2019;Uzuner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity in bone shapes among ruminants living in these different habitats and climates has not yet been fully determined. In recent years, studies examining the morphometric structures of the distal phalanx have been undertaken [6][7][8]. These studies contribute to the literature's knowledge in terms of taxonomy and help explain the variations in the distal phalanx.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic morphometry is a widely used research method for sex determination in humans (Suzuki et al, 2020; Uzuner et al, 2016) and domestic mammals (Gündemir et al, 2021) but has not yet been reported in poultry.…”
Section: Introductionmentioning
confidence: 99%